Strong positively diversity–productivity relationships in the natural sub-alpine meadow communities across time are up to superior performers - Jiang, Kai (Sci Rep, 2020)
In experiments that test plant diversity–productivity relationships, the common practice of weeding unsown species and disallowing species colonization may have the unintended consequence of favoring priority effects that maintain niche complementarity in determining productivity. However, in naturally assembled communities where colonization occurs, resource competition may favor dominant traits, which eventually have the greatest influence on productivity. Here, in naturally developed long-term subalpine meadows (from 4-year to at least 40 years meadows) in the Qinghai-Tibetan Plateau, we investigated the relationships between species richness and productivity to testify whether positive diversity–productivity relationships can still exist in naturally developed long-term communities. We also measured five functional traits (specific leaf area, photosynthesis rate, leaf proline content, seed mass and seed germination rate) to calculate two functional diversity indices: community-weighted mean trait values (CWM) and Rao’s quadratic entropy (RaoQ) which are highly correlated to functional traits of dominating species and variety of functional trait among all species. Finally, we quantified the relative contribution of species diversity, functional traits of dominating species and functional diversity among all species to productivity along the succession. We demonstrated strong positively diversity–productivity relationships in the natural sub-alpine meadow communities across time. The five traits of dominating species explained a large proportion (54–80%) of the variation in productivity during succession, whereas species diversity and functional diversity (FD) for each of the five traits explained much less (24–48% for species richness and 0–40% for FD for each of the five traits respectively). We found unequivocal evidence that significantly positive diversity–productivity relationships in the natural sub-alpine meadow communities across time are up to superior performers (dominant traits) in naturally developed communities where colonization occurs. As a result, understanding diversity–productivity relationships under the full range of community assembly processes therefore merits further investigation.